EFFECTS OF MARKET RISK ON PERFORMANCE OF TRANSPORT FIRMS IN KENYA - Noor, Jamal Ali Mohamed; Njeru, Dr. Agnes; Muoria, Dr. Esther (IJRDO - Journal of Business Management, 2017)
This study assessed market risk effects on performance of transport firms in Mombasa County. The study employed triangulation (Mixed of quantitative and qualitative) research design. The target population of this study was 2013 transport firms and the sample size was 172 firms arrived at through stratified and purposive sampling methods. The questionnaire was the primary data tool. The study found out that market risk has significant effects on financial performance of transport firms in Kenya. Also the study indicated that given the infrastructure development as part of the Vision 2030, Transport firms need to embrace change so that they are not wiped out of the market. Thus engage in competitive nature by also bringing in the market competitive services to offer to their clients and share the growing market